The new North American studies : culture, writing and the politics of re/cognition - Siemerling, Winfried, 1956- (Routledge, 2005)
"In this study, Winfried Siemerling examines the complexities of recognition and identity, rejecting previous nationalized thinking to approach North American cultural transformations from transnational and interdisciplinary perspectives." "Using material from the United States and Canada as case studies and drawing on a wide range of texts and theorists, he examines postcoloniality and cultural emergence from the sixties to the present against earlier backgrounds."--Jacket